Low Luteal Serum Progesterone Levels Are Associated With Lower Ongoing Pregnancy and Live Birth Rates in ART: Systematic Review and Meta-Analyses - Ranisavljevic, Noemie; Huberlant, Stephanie; Montagut, Marie; Alonzo, Pierre-Marie; Darné, Bernadette; Languille, Solène; Anahory, Tal; Cédrin-Durnerin, Isabelle (Frontiers in Endocrinology, 2022)
Progesterone plays a key role in implantation. Several studies reported that lower luteal progesterone levels might be related to decreased chances of pregnancy. This systematic review was conducted using appropriate key words, on MEDLINE, EMBASE and the Cochrane Library, from 1990 up to March 2021 to assess if luteal serum progesterone levels are associated with ongoing pregnancy (OP) and live birth (LB) rates (primary outcomes) and miscarriage rate (secondary outcome), according to the number of corpora lutea (CL). Overall 2,632 non-duplicate records were identified, of which 32 relevant studies were available for quantitative analysis. In artificial cycles with no CL, OP and LB rates were significantly decreased when luteal progesterone level falls below a certain threshold (risk ratio [RR] 0.72; 95% Confidence interval [CI] 0.62-0.84 and 0.73; 95% CI 0.59-0.90, respectively), while miscarriage rate was increased (RR 1.48; 95% CI 1.17-1.86). In stimulated cycles with several CL, mean luteal progesterone level in no OP and in no LB groups was significantly lower than in OP and LB groups [difference in means 68.8 (95% CI 45.6-92.0) and 272.4 (95% CI 10.8-533.9), ng/ml, respectively]. Monitoring luteal serum progesterone levels could help individualizing progesterone administration to enhance OP and LB rates, especially in cycles without corpus luteum.